2017
DOI: 10.1002/chir.22677
|View full text |Cite
|
Sign up to set email alerts
|

Helical screw sense bias in chiral polyfluorene stimulated by solvent

Abstract: Conjugated homopolymer poly(9,9-bis(3-((S)-2-methylbutylpropanoate))fluorene) (PSF) with chiral pendants was synthesized and characterized. Dissolution experiments show that PSF is well dissolved in racemic limonene at high temperature and begins aggregating upon sequential cooling treatment. The corresponding assemblies were transferred to quartz plate by the spin-coating method. Comparably, film casting from chloroform solution was also prepared. Upon annealing thermal treatments, these PSF films exhibited p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Nakano et al studied neomenthyl-functionalized polyfluorenes; in particular, the alternating copolymer 84 having chiral 9-neomenthyl-9- n -pentyl-fluoren-2,7-diyl and achiral 9,9-bis- n -octyl-fluoren-2,7-diyl units showed g abs factor maximum value of 2.6 × 10 –2 at 393 nm in drop-casted films after 48 h at 160 °C . Moreover, polyfluorene 85 with 3-(( S )-2-methylbutyl)­propanoate chains as chiral pendant was characterized in spin-coated thin films as neat material and as aggregates blended with racemic limonene (Figure ). Very recently, Huang and co-workers instead developed a set of aryl-substituted polyfluorenes, as ultrastable supramolecular self-encapsulated wide-bandgap semiconductors for electroluminescent devices; in particular, ECD spectra of thin films casted from toluene solution confirmed that self-assembled gelation structure of the polymers exhibited a helical organization …”
Section: Ecd Properties In Thin Films Of π-Conjugated Systems: Litera...mentioning
confidence: 99%
“…Nakano et al studied neomenthyl-functionalized polyfluorenes; in particular, the alternating copolymer 84 having chiral 9-neomenthyl-9- n -pentyl-fluoren-2,7-diyl and achiral 9,9-bis- n -octyl-fluoren-2,7-diyl units showed g abs factor maximum value of 2.6 × 10 –2 at 393 nm in drop-casted films after 48 h at 160 °C . Moreover, polyfluorene 85 with 3-(( S )-2-methylbutyl)­propanoate chains as chiral pendant was characterized in spin-coated thin films as neat material and as aggregates blended with racemic limonene (Figure ). Very recently, Huang and co-workers instead developed a set of aryl-substituted polyfluorenes, as ultrastable supramolecular self-encapsulated wide-bandgap semiconductors for electroluminescent devices; in particular, ECD spectra of thin films casted from toluene solution confirmed that self-assembled gelation structure of the polymers exhibited a helical organization …”
Section: Ecd Properties In Thin Films Of π-Conjugated Systems: Litera...mentioning
confidence: 99%
“…However, the difference in solubility could even induce conformation-driven mirrorimage supramolecular chirality isomerism by confining the intrinsically chiral macromolecules in a metastable -phase. [15] In addition to solvent properties, other factors like pH and metal ions could alter the environment of the solution systems, further exerting profound impacts on the transfer and expression of chirality. Yashima et al reported the extension and contraction motions of the spiroborate-based double-stranded helicates composed of 4,4′-linked 2,2′-bipyridine and its N,N′-dioxide units in the middle of ortho-linked tetraphenol strands, which are regulatable by the binding and releasing of protons or metal ions, as shown in Figure 2A.…”
Section: Assembly Of Chiral Molecules In Achiral Solventsmentioning
confidence: 99%
“…However, the difference in solubility could even induce conformation‐driven mirror‐image supramolecular chirality isomerism by confining the intrinsically chiral macromolecules in a metastable β ‐phase. [ 15 ] In addition to solvent properties, other factors like pH and metal ions could alter the environment of the solution systems, further exerting profound impacts on the transfer and expression of chirality. Yashima et al.…”
Section: Supramolecular Chirality Transfer In Solution Systemsmentioning
confidence: 99%
“…The chiroptical activity of PFs is not unambiguous and a plethora of (large) chiral responses have been reported. , The chiral supra- and macromolecular structure of PFs, and therefore the chiral expression, is governed by the interplay between inter- and intramolecular interactions . When the organization of the PF is governed by intermolecular interactions, a bisignate Cotton effect is expected as a result of exciton coupling between two/multiple interacting chromophores.…”
Section: Introductionmentioning
confidence: 99%